Optimizing purity and recovery of biogas methane enrichment process in a closed landfill. (February 2019) - Seman, S.Z.A.; Idris, I.; Abdullah, A.; Shamsudin, I.K.; Othman, M.R.
Abstract: Biogas calorific value upgrading into biomethane or methane-rich gas is an attractive choice for renewable energy alternatives. Exploitation of methane-rich gas from landfill has gained increasing traction recently due to its fuel source diversification potential towards carbon neutrality and energy security. In this paper, methane enrichment process in a membrane plant from a biogas mixture containing methane, carbon dioxide, nitrogen, oxygen, hydrogen sulfide and water vapor was modeled and compared with the actual plant data. Results from this work reveal an interesting relationship between purity-recovery and the process operating conditions. The model was capable of simulating the methane enrichment effectively with merely 0.07% error in predicting methane purity and 0.52% error in predicting methane recovery. The model allows optimization of methane purity from 87.26% to 99.87% and methane recovery from 91.63 to 99.49% at permeate to feed ratio (stage cut) of 0.30, without the need for re-staging of the plant. Highlights: Biogas upgrading in a membrane plant was modeled and compared with actual plant setting. Model predicts methane enrichment with less than 1% error without re-staging. CH4 purity and recovery optimization of 99.87% and 99.49%, respectively at 0.30 stage cut.